Cardiovascular Disease Risk Factors in Hispanic Adolescents in South Texas. Issue 2 (February 2016) - Cooper, Sharon P.; Shipp, Eva M.; del Junco, Deborah J.; Cooper, Charles J.; Bautista, Leonelo E.; Levin, Jeffrey
Abstract : Objectives: Despite a national crisis of increased prevalence of obesity and type 2 diabetes mellitus in adolescents, especially among Hispanics, there is a paucity of data on health indicators among farmworker adolescents and their peers. The main aim of this study was to estimate the prevalence of cardiovascular disease risk factors in a population of Hispanic adolescent students in south Texas. The study also aimed to compare the prevalence of these risk factors between students enrolled in the Migrant Education Program (MEP) and other students, and between boys and girls. Methods: In partnership with the Weslaco (Texas) Independent School District and the Migrant Education Department, a cohort study was conducted from 2007 to 2010 to estimate the prevalence of overall obesity (body mass index ≥85th percentile for age and sex), abdominal obesity (waist circumference ≥75th percentile for age, sex, and ethnicity), acanthosis nigricans (AN), and high blood pressure (HBP; ≥90th percentile for age, height, and sex or systolic/diastolic BP ≥120/80 mm Hg) among MEP students compared with other students from two south Texas high schools. Multilevel logistic regression was used to assess the relation between sex and our main outcomes of interest while accounting for within-school nesting of participants. Results: Among 628 sampled students, 508 (80.9%) completed the consent procedure and participated in the study. Of these, 257 were MEP students and 251 were non-MEP peers. Approximately 96.7% of participants were Hispanic and 50.0% were boys. Analyses of data across the years comparing MEP students and non-MEP students show an average prevalence of 44.8% versus 47.7% for overall obesity, 43.2% versus 43.7% for abdominal obesity, 24.7% versus 24.7% for AN, and 29.2% versus 32.8% for HBP. Across recruitment and follow-up years, the prevalence of overall obesity, abdominal obesity, and HBP was 1.3 to 1.5, 1.2 to 1.8, and 2.9 to 4.6 times higher in boys than in girls, respectively. In contrast, the prevalence of AN varied little by sex. Conclusions: The high prevalence of cardiovascular risk factors in both groups suggests a compelling need for comprehensive, culturally targeted interventions to prevent future cardiovascular diseases in these high-risk Hispanic adolescents, especially among boys. There were not, however, substantial differences between MEP students and other students. These findings also support the feasibility of conducting future epidemiologic studies among adolescent farmworkers and their families, as well as culturally appropriate school or community-based interventions. Abstract : Despite the increased prevalence of obesity and type 2 diabetes mellitus in adolescents, especially among Hispanics, there is a paucity of data on health indicators among farmworker adolescents and their peers. We conducted a cohort study from 2007 to 2010 to estimate the prevalence of overall obesity (body mass index ≥85th percentile for age and sex), abdominal obesity (waist circumference ≥75th percentile for age, sex, and ethnicity), acanthosis nigricans, and high blood pressure (≥90th percentile for age, height, and sex or systolic/diastolic blood pressure ≥120/80 mm Hg) among Migrant Education Program students compared with other students from two south Texas high schools.